1997
DOI: 10.1111/j.1440-1681.1997.tb01232.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF SARAFOTOXIN S6c ON RENAL HAEMODYNAMICS AND URINE FORMATION IN ANAESTHETIZED DOGS

Abstract: 1. The effects of sarafotoxin S6c (S6c), a selective endothelin ETB receptor agonist, on renal haemodynamics and urine formation were examined in anaesthetized dogs. 2. Intrarenal arterial infusion of S6c at a rate of 1 or 5 ng/kg per min produced a transient increase in renal blood flow (RBF), with no change in systemic blood pressure and heart rate; RBF then decreased gradually to below the basal value. There were significant and dose-dependent increases in urine flow and free water clearance and decreases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…26 In the present study, we cannot identify the downstream of ET B receptor stimulation, but CF after ischemia/reperfusion markedly increased after treatment with big ET-1, possibly implicating vasorelaxing factor(s). In addition, we have recently reported that nitric oxide has an inhibitory effect on NE overflow after cardiac ischemia/reperfusion.…”
Section: Discussioncontrasting
confidence: 61%
“…26 In the present study, we cannot identify the downstream of ET B receptor stimulation, but CF after ischemia/reperfusion markedly increased after treatment with big ET-1, possibly implicating vasorelaxing factor(s). In addition, we have recently reported that nitric oxide has an inhibitory effect on NE overflow after cardiac ischemia/reperfusion.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, the ability of the ET B receptor to reduce renal tubular transport has been attributed to increasing NO (22). Matsuo and colleagues (17) have also reported that S6c infusion in the renal artery of anesthetized dogs results in a natriuretic and diuretic effect that is also associated with increases in urinary excretion of NO metabolites, nitrate and nitrite. A lingering question has been which NOS isoform could be involved in the proexcretory effects of ET B receptor stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…Nitric oxide (NO) is thought to act as the downstream mediator of renal ET B receptor activation, because total NO synthase (NOS) inhibition can inhibit ET B receptor-dependent responses both in vivo (17) and in vitro (22). However, which NOS isoform is mainly involved in ET B -mediated diuretic and natriuretic responses remains unclear because all three NOS isoforms are expressed in tubules within the renal medulla (18,33).…”
mentioning
confidence: 99%
“…ETA and ETB receptors expressed in tubular cells contribute to the regulation of electrolyte and water homeostasis, which have profound implications for regulation of arterial blood pressure. There is conflicting data regarding the presence and function of ETA and ETB in specific nephron segments, but the main conclusion is that ETA serves as vasoconstrictor in the vascular beds effecting RBF, GFR and mainly cortical RBF whereas ETB are more involved in the regulation of water and sodium homeostasis by regulating medullary RBF and directly inhibiting tubular transport [47,48]. ETBmediated natriuresis and diuresis are reported to involve several different cellular signaling pathways, including protein kinase C, mitogen activated protein kinase and cyclooxygenase.…”
Section: The Endothelin Systemmentioning
confidence: 99%